2012
DOI: 10.1097/qai.0b013e318271799b
|View full text |Cite
|
Sign up to set email alerts
|

Serum (1→3)-β-D-Glucan Levels in HIV-Infected Individuals Are Associated With Immunosuppression, Inflammation, and Cardiopulmonary Function

Abstract: Background Translocation of gastrointestinal bacteria in HIV-infected individuals is associated with systemic inflammation, HIV progression, mortality, and co-morbidities. HIV-infected individuals are also susceptible to fungal infection and colonization, but whether fungal translocation occurs and influences HIV progression or co-morbidities is unknown. Methods Serum (1→3)-β-D-glucan was measured by a Limulus Amebocyte Lysate assay (Fungitell®) in 132 HIV-infected outpatients. Selected plasma cytokines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 40 publications
8
68
2
Order By: Relevance
“…Our results confirm findings of a previous study, that evaluated BDG levels in a cohort of in HIV-infected outpatients (majority not virologically suppressed) and found that plasma IL-8 (p=0.03), and TNF-α (p=0.03) were increased in those with high BDG levels (i.e. >40 pg/mL), while IL-6 was not significantly different [5]. Another study that evaluated BDG as a marker for cryptococcal meningitis among HIV-infected individuals in cerebrospinal fluid (CSF) (21) found positive correlations between BDG and IL-8 (p<0.01), and also TNF-α (p=0.02), while again no correlation was found with IL-6 [21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results confirm findings of a previous study, that evaluated BDG levels in a cohort of in HIV-infected outpatients (majority not virologically suppressed) and found that plasma IL-8 (p=0.03), and TNF-α (p=0.03) were increased in those with high BDG levels (i.e. >40 pg/mL), while IL-6 was not significantly different [5]. Another study that evaluated BDG as a marker for cryptococcal meningitis among HIV-infected individuals in cerebrospinal fluid (CSF) (21) found positive correlations between BDG and IL-8 (p<0.01), and also TNF-α (p=0.02), while again no correlation was found with IL-6 [21].…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown previously that BDG levels were markedly higher (mean 142 pg/mL) in a HIV infected cohort with lower median CD4 counts (26, IQR 10–53, all without opportunistic infections), when compared to the cohort studied here (with a median CD4 count >600 pg/mL) [13]. In another study, high serum BDG levels (>40 pg/mL) were more likely to occur in individuals with CD4 counts less than 200 cells/mL (31.8% vs. 8.4%, p<0.01), higher HIV viral levels (2.85 vs. 2.13 log 10 copies/mL, p<0.01), and those without ART (68.2% vs. 90.0%, p<0.01) [5]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1→3)-b-D-glucan (BG) is a component of fungal cell walls that is shed into the blood and can be detected in the serum of patients with fungal pneumonia (37,38). We have recently found detectable BG levels in HIVinfected adult outpatients without pneumonia, and BG levels correlate strongly with airway obstruction, DL CO , echocardiographic pulmonary artery pressures, higher inflammatory cytokines, increased sputum neutrophils, and activated peripheral lymphocytes (39). These results indicate that fungal translocation is an unrecognized contributor to inflammation and chronic complications of HIV.…”
Section: Fungi As Possible Agents Of Microbial Translocationmentioning
confidence: 91%